Pour une histoire de l’enseignement agricole féminin durant les années 1950-60 : les écoles ménagères agricoles du Loir-et-Cher ou l’éducation contrariée au rôle de femme d’exploitant - Jérôme Pelletier (Genre & Histoire)
At the moment of France’s Liberation the agricultural world made important steps to join the modernizing efforts of the country. This article explores the role of technical education offered to farmers’ daughters who intended to become farmers themselves. It shows how training within agricultural home economic schools, which had emerged in the interwar period and flourished under Vichy, both adapted to and responded to the requirements of the profession that sought to renew the model of the family farm. This involved an increasingly gendered definition of what constituted a woman farmer’s area of expertise. Research at the departmental level reveals the characteristics of this process during the two decades that refashioned French agricultural life. Above all it shows how local actors used the means available to them to divert some of the objectives of this training.